The Disability Scenario in India: A Reality Check - ​Bhawna Kothari; ​Meena Galliara; Ratna Huirem (Journal of Social Work Education and Practice, 2023)
Are disabled people truly included in Indian society? This is a question that needs to acquire even greater thrust in the wake of the COVID-19 pandemic where “health” per se has become a wild goose chase even for the abled. This paper is based only on literature review and tries to examine and assess the current situation of the disabled in India. The first part provides conceptual clarity to the definition as well as perspectives of disability and a brief description of the disability scenario at the global and national levels. An overview of the disability rights movements, legal provisions, and policy measures adopted by the government to change the focus from disability to the ability to facilitate inclusion is presented in the ensuing part. This is followed by a discussion on the assessment of disability inclusion. The paper ends with an analysis of the inclusion assessment measures, conclusion, and what could be the road ahead.